1997
DOI: 10.1017/s0033291796004175
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic reasoning in obsessive–compulsive and delusional disorders

Abstract: Our findings extend those of others but require cautious interpretation as to the role of probabilistic reasoning in the genesis of delusions or obsessions. Obsessionals in both the OCD and Mixed groups, showed substantial deviation from Bayesian norms, suggesting that obsessionality leads to a reasoning style that is less 'normal' than that of delusionals. Further work is required to investigate clinical correlates of these findings which provide modest support for the proposal that the combination of obsessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
107
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 14 publications
19
107
1
5
Order By: Relevance
“…For part 2 of the beads task, certainty percentages were collected for each bead, as in Fear and Healy (1997). This yielded four measures: Max1, Max2, Jar Change, and Beads to Change (BTC).…”
Section: Beads Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…For part 2 of the beads task, certainty percentages were collected for each bead, as in Fear and Healy (1997). This yielded four measures: Max1, Max2, Jar Change, and Beads to Change (BTC).…”
Section: Beads Taskmentioning
confidence: 99%
“…Indeed, delusional schizophrenia patients were more likely than nondelusional psychiatric controls and non-patients to reduce their level of certainty when presented with disconfirmatory evidence. Other studies did not find differences between the way delusional and control groups reacted to disconfirmatory evidence (Dudley et al, 1997;Fear and Healy, 1997;Young and Bentall, 1997;Peters and Garety, 2006). One study in healthy participant found that people with high scores of delusional ideation were also more reactive to a piece of disconfirmatory evidence than people with low scores (Colbert and Peters, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…A more likely explanation of reduced sensitivity to diversity in the OCD-high group relates to preservative tendencies observed in other studies of probabilistic and inductive reasoning in OCD patients (e.g. Fear & Healy, 1997;Volans, 1976). Such studies have found that when asked to evaluate evidence for an uncertain conclusion, people with OCD-related traits often repeatedly choose to examine similar or redundant types of evidence.…”
Section: Discussionmentioning
confidence: 88%
“…However, if inductive reasoning is impaired in people with OCD, then we would expect to see less evidence of the diversity heuristic in those with OCD symptoms. Indirect support for this prediction comes from the finding that relative to controls, individuals with OCD often make repeated observations of the same or similar items before making a probability judgment (e.g., Fear & Healy, 1997;Volans, 1976). As shown in Table 2, the prediction about differences between diversity-based reasoning in those low or high in OCD traits was examined using "OCD-neutral" arguments as well as arguments with content relevant to common obsessions (OCD-relevant).…”
Section: ________________ Jill Gets Cleanmentioning
confidence: 99%
See 1 more Smart Citation